(untitled) (Applied Biological Research, 2023)
Escherichia coli and Proteus mirabilis are Gram-negative, rod-shaped uro pathogens that frequently cause urinary tract infections. They have gained importance due to the emergence of multi-drug resistance in them. This work compares the antibiotic resistance pattern of clinical isolates of E. β-lactam resistance mechanism. The antibiotic susceptibility of E. coli and P. mirabilis was assessed by Kirby-Bauer disc diffusion assay. Extended spectrum β-lactamase was detected by a modified double-disc synergy test and EZY MICTM strip test. The amplification of drug-resistant gene was done by PCR. The role of efflux pump was determined by using the efflux pump inhibitor, carbonyl cyanide 3-chlorophenylhydrazone (CCCP). The results of antibiotic susceptibility test indicated multi-drug resistant phenotypes along with tetracycline and β-lactam resistance. E. coli was found to be extended-spectrum β-lactamase producer; whereas P. mirabilis yielded negative result. PCR results showed the presence of tetA gene in E. Further, efflux pump assay using efflux inhibitor CCCP proved that the efflux mechanism causes tetracycline resistance. The study necessitates the continuous monitoring of antimicrobial drug resistance in uropathogens for better therapeutic approaches to curtail the risk of AMR.